A new Chinatown? Authenticity and conflicting discourses on Pracha Rat Bamphen Road. Issue 9 (20th October 2020) - Wu, Hongmei; Techasan, Sethawut; Huebner, Thom
ABSTRACT: Chinatowns around the world have been much studied in the linguistic landscape literature. The bulk of this research has focused on Western enclaves resulting from the Chinese diaspora of the Nineteenth Century, which share certain semiotic characteristics and histories. Less research has been conducted on Chinatowns in the East or on newly emerging Chinese enclaves. This study, framed by Lefebvre's Production of Space, fills a gap by investigating a newly emerging Chinatown in Bangkok, in contrast to that city's original Chinatown of Yaowarat, and to those of the nineteenth century diaspora. In asking the question, 'what constitutes an authentic Chinatown, and in whose eyes', it draws on data from field trips, photographs, interviews, questionnaires, focus group and documents to highlight how this neighbourhood differs in important ways from Yaowarat and how both are distinct from diasporic Chinatowns and from more recent Chinese enclaves. The study re-examines the notion of authenticity as applied to Chinatowns and identifies a number of distinct discourses revealing opposing conceptions of authenticity.